Thermodynamics of radical scavenging of symmetric carotenoids and their charged species. (1st December 2018) - Poliak, Peter; Škorňa, Peter; Klein, Erik; Lukeš, Vladimír
Highlights: Carotenoids, their charged species and radicals are investigated. Thermodynamically preferred sites of antioxidant activity are identified. Antioxidant/pro-oxidant behavior is related to studied reaction enthalpies. Effect of the solvent polarity on studied reaction pathways is analyzed. Abstract: For nine symmetric natural carotenoids, a comprehensive thermodynamics study of processes associated with their radical scavenging activity is proposed. We have investigated the hydrogen atom transfer (HAT) from the parent carotenoid, mono-radical species, radical cations and radical anions. Electron transfer and proton transfer reactions were also studied. Terminal units and carbon atoms in their vicinity were identified as thermodynamically favoured reaction sites of the HAT mechanism. Rhodoxanthin, canthaxanthin and astaxanthin, as strong antioxidants, without any pro-oxidative effect, were found to have bond dissociation enthalpies (BDE) higher than 300 kJ mol −1 and the most negative electron affinities. The electron transfer to a carotenoid is exothermic, while other studied reactions are endothermic. In solvent, the electron transfer reactions may be preferred instead of hydrogen atom transfer.